2020
DOI: 10.3892/ol.2020.11259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nalbuphine on patient controlled intravenous analgesia after radical resection of colon cancer

Abstract: Effect of nalbuphine on patient-controlled intravenous analgesia (PCIA) after radical resection of colon cancer was explored. Retrospective analyses of 100 patients who underwent elective laparoscopic radical resection of colon cancer in Xiang Yang No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…27 This may be attributed to its central antagonist activity on μ-receptors. 28 Several studies have shown that the analgesic e cacy of nalbuphine is comparable to that of morphine, but nalbuphine provides a better safety pro le than morphine for PONV and pruritus, 29,30 which is consistent with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…27 This may be attributed to its central antagonist activity on μ-receptors. 28 Several studies have shown that the analgesic e cacy of nalbuphine is comparable to that of morphine, but nalbuphine provides a better safety pro le than morphine for PONV and pruritus, 29,30 which is consistent with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…19 This may be attributed to its central antagonist activity on μ-receptors. 28 Several studies have shown that the analgesic e cacy of nalbuphine is comparable to that of morphine, but nalbuphine provides a better safety pro le than morphine for PONV and pruritus, 29,30 which is consistent with our ndings.…”
Section: Discussionsupporting
confidence: 86%
“…Nalbuphine is an opioid analgesic that was first manufactured in the 1970s and has been used to induce analgesia, similar to other opioids 1–3 . As a “neutral” mu (μ) receptor antagonist, nalbuphine induces various opioid‐related side effects, including pruritus, respiratory depression and urinary retention at low dose 4 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In the drug instructions for Nubain ® , nalbuphine is recommended to be administered every 3–6 h if necessary. Importantly, PCA is commonly used in clinical postoperative analgesia, and nalbuphine application via PCA had been reported in several reports 3,17–19 . However, differences in the pharmacokinetics of nalbuphine administered via single injection or PCA are still unclear.…”
Section: What Is Known and Objectivementioning
confidence: 99%